Fractured Truth Between the Border and Broadcasts – The PostTruth Gaze of Indian Media on Bangladeshi Hindus After the July Uprising - Snigdha, Rezwana Karim; Zohra, Fatema Tuz (The Jahangirnagar Review, 2025)
This paper emphasises the intersectional lens of disinformation and misinformation of Indian media about the July Movement 2024 in Bangladesh. It highlights how Indian media are constructing post-truth realities of Bangladeshi Hindus after the July Movement 2024. It explores the way Indian media are exploiting the digital, social, and printing media platforms. Furthermore, this paper represents how fabricated and manipulative news creates a hyperreality about the events of the July Movement 2024 in Bangladesh. The primary objective of this study is to explore how Indian media circulate disinformation and misinformation and produce manipulative narratives to create hyperreality about the Bangladeshi Hindu after the July Movement 2024, which has replaced political unrest with religious and anti-democratic sentiments. Data were collected and analysed using content analysis to explore power dynamics, biases, and identity politics. This paper also illustrates how historical contexts and politics of othering have made the circulation and consumption of disinformation and misinformation plausible. Lastly, it mentions how the agency and subjectivity of images, the monetary system of social media, and other external and internal factors drive various actors to construct the post-truth reality of Bangladeshi Hindus through disinformation and misinformation.